2016
DOI: 10.3389/fncir.2016.00108
|View full text |Cite
|
Sign up to set email alerts
|

Reboxetine Improves Auditory Attention and Increases Norepinephrine Levels in the Auditory Cortex of Chronically Stressed Rats

Abstract: Chronic stress impairs auditory attention in rats and monoamines regulate neurotransmission in the primary auditory cortex (A1), a brain area that modulates auditory attention. In this context, we hypothesized that norepinephrine (NE) levels in A1 correlate with the auditory attention performance of chronically stressed rats. The first objective of this research was to evaluate whether chronic stress affects monoamines levels in A1. Male Sprague–Dawley rats were subjected to chronic stress (restraint stress) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 62 publications
0
5
0
2
Order By: Relevance
“…In adult rats exposed to variable prenatal stress, deficits in attentional responses were found in a variant of the 5-CSRTT, and these deficits were corrected in a dose-dependent manner by the norepinephrine reuptake inhibitor atomoxetine (Wilson et al 2012). Other studies have shown that auditory attention impaired by chronic restraint stress is alleviated by reboxetine, another norepinephrine reuptake inhibitor (Perez-Valenzuela et al 2016).…”
Section: Attentionmentioning
confidence: 99%
“…In adult rats exposed to variable prenatal stress, deficits in attentional responses were found in a variant of the 5-CSRTT, and these deficits were corrected in a dose-dependent manner by the norepinephrine reuptake inhibitor atomoxetine (Wilson et al 2012). Other studies have shown that auditory attention impaired by chronic restraint stress is alleviated by reboxetine, another norepinephrine reuptake inhibitor (Perez-Valenzuela et al 2016).…”
Section: Attentionmentioning
confidence: 99%
“…Interestingly, another type of stress-social stress-induced an increase in IHC ribbon synapses [65]. Furthermore, repeated injections might also be a source of anxiety for animals [93]. In the process of data evaluation, we compared hearing thresholds at baseline between mock-injected and non-injected animals and found that the injected rats had higher hearing thresholds by about 10-20 dB [61][62][63][64], which has so far not been reported.…”
Section: Discussionmentioning
confidence: 92%
“…Выраженные прокогнитивные свойства выявлены у упомянутого выше антидепрессанта ребоксетина. Так, в экспериментах на крысах, подвергавшихся хроническому стрессу, выявлена способность данного соединения улучшать показатели внимания [27]. Доказана эффективность ребоксетина при СДВГ у детей.…”
Section: обзорыunclassified